PROJECT MANAGEMENT STANDARDS IN EVALUATING THE EFFICIENCY OF CIVIL SERVANTS ("Mehnat iqtisodiyoti va inson kapitali" ilmiy elektron jurnali, 2023)
This article analyzes the prospects of using project management standards in human resource management. Modern approaches to evaluating the performance of civil servants were discussed. The main direction, theory and international practice of improving the efficiency of civil servants were studied and researched.
Keywords: human resources, project management, civil servants, efficiency, perspective, approach, direction, standard.